Presentation success how to plan, prepare, and deliver effective presentations - Chan, Janis Fisher (American Management Association, 1999)
What does it take to impress an audience? No more boring presentations! Presentation Success gives you what it takes to succeed-spectacularly-when you stand up to impress an audience. Packed with easy-to-use worksheets, strategies, and tips, this book delivers success. It helps you overcome ""presentation fear"" and makes it easy to plan, prepare, and deliver the kind of presentations that make people sit up and take notice. You'll discover the best ways to prepare your opening, write smooth transitions, plan your Q & A session, and troubleshoot potential problem areas. You'll learn how to use b